Fostering organizational performance through innovation: The roles of environmental policy instruments, organizational learning supports, and intellectual capital - Thang Nam Huynh; Phuong Van Nguyen; Anh Minh Do; Phuong Uyen Dinh; Huan Tuong Vo (Heliyon)
This study aimed to examine the key factors that influence entrepreneurial innovation and organizational performance, specifically focusing on the impact of environmental policy instruments, intellectual capital, and organizational learning. In the context of the resource-based view and institutional theory, the authors developed a comprehensive research model to establish hypotheses about the relationships between these factors. Utilizing a survey-based technique with random sampling, this study analyzes the complex relationships between variables by employing structural equation modeling. Data were obtained from 323 members of management teams from Vietnamese firms. The results emphasize the significant advantage of accruing intellectual capital and fostering organizational learning in response to the impact of environmental policy instruments on entrepreneurial innovation. Furthermore, integrating intellectual capital, entrepreneurial innovation, and organizational learning is shown to improve organizational performance. Entrepreneurial innovation plays a role in connecting organizational performance with intellectual capital and organizational learning. The study’s findings provide valuable insights for scholars and professionals, enhancing comprehension of complex interactions among various elements. Entrepreneurs can utilize these observations to develop inventive tactics that harness both internal and external resources to effectively promote innovation and improve business performance.